Empowerment of Jamu Gendong Entrepreneurial Community in Pangkalpinang - Sudirman, Muhamad Seto; Purba, Eva Dewi R; R, Afif Fajri (PT FORMOSA CENDEKIA GLOBAL, 2024)
Traditional jamu carrying is made using simple traditional processes, such as washing with clean water, peeling, grating, stamping, boiling, filtering, and other processes. The activity was carried out in two stages. In February 2023, coordination, permitting, and surveys were carried out. The implementation and evaluation of community service is carried out in the second week of April to Sunday. Entrepreneurs in Pangkalanbaru District gained a better understanding of NIB, Brand Rights, and the legality of making NIB, the benefits they obtained when registering their business after the NIB business actors obtained legality for their business.